Education As My Agenda - Robinson, J. author. aut Link
XII, 311 p.
Keywords: When Gertrude Williams retired in 1998, after forty-nine years in the Baltimore public schools,The Baltimore Sun called her "the most powerful of principals" who "tangled with two superintendents and beat them both." In this oral memoir, Williams identifies the essential elements of sound education and describes the battles she waged to secure those elements, first as teacher, then a counselor, and, for twenty-five years, as principal. She also described her own education - growing up black in largely white Germantown, Pennsylvania; studying black history and culture for the first time at Cheyney State Teachers College; and meeting the rigorous demands of the program which she graduated from in 1949. In retracing her career, Williams examines the highs and lows of urban public education since World War II. She is at once an outspoken critic and spirited advocate of the system to which she devoted her life.